Symbolic Meaning in Traditional Badudus Pangantin Banjar - Kamariah; Nanda Saputra (LingLit Journal Scientific Journal for Linguistics and Literature, 2020)
This research examines the cultural symbols used in the badudus pangantin Banjar custom. The approach used is a cultural semiotics approach. namely studies that emphasize the symbols of a culture. The method used is descriptive analysis method. The primary data source was obtained from four resource persons in the Peat District, aged 60-75 years. Data collection techniques are in the form of (1) observation, (2) interviews, (3) recording, (4) recording. The data analysis technique used is descriptive qualitative. The results of this study show that the symbolic meanings of the Banjar bridal shower custom are as follows: a. symbol of baras longitude, banana, spray three times, tapih, mayang, banyu prayer, candle, carmin, bamantra oil, white porridge, black porridge and pupur with the meaning of a blessed life bride, b. palm symbol, starting with the right, and kambang malati, meaning good behavior. c. symbol of baras lakatan, habang sugar and hintalu with the meaning of living together.